Friends with God?: Moses and the Possibility of Covenantal Friendship - Lapsley, Jacqueline E. (Interpretation, 2004)
The friendship shared by Moses and God offers a more appropriate model of faithfulness than Israel's prescribed obedience. The intimacy of their relationship offers an alternative model for the church's relationship to God, a countercultural “covenantal friendship.”